Quantification of branching within high molecular weight polymers with polyester backbones formed by transfer-dominated branching radical telomerisation (TBRT). Issue 39 (12th July 2021) - Cassin, Savannah R.; Flynn, Sean; Chambon, Pierre; Rannard, Steve P.
Abstract : The characterisation and quantification of branching is key to understanding new complex macromolecules. Here we establish approaches to evaluate the unique and novel architectures formed by Transfer-dominated Branching Radical Telomerisation (TBRT). Abstract : New branched polymerisations offer previously inaccessible macromolecules and architectural understanding is important as it provides insight into the branching mechanism and enables the determination of structure–property relationships. Here we present a detailed inverse gated 13 C NMR characterisation of materials derived from the very recently reported Transfer-dominated Branching Radical Telomerisation (TBRT) approach to quantify branching and provide an insight into cyclisation.